A Novel Adaptive Directional Interpolation Algorithm for Digital Video Resolution Enhancement. (15th December 2020) - Sun, Dong; Xie, Qingqing; Li, Teng; Lu, Yixiang; Zhu, De; Gao, Qingwei
Abstract : In this paper, a novel digital video resolution enhancement algorithm based on adaptive directional interpolation is proposed, where the directionality of the edge structure and the nonlocal self-similarity prior within the current frame as well as its adjacent frames are both considered. First, we establish the regularization equation that conforms to the prior model of a video frame and then take the classic bicubic interpolation result as the initial estimation to iteratively solve the restoration equation, in which the edge structures and contours in low resolution (LR) input are reconstructed to estimate and refine the desired high resolution (HR) output. Experimental results show that the proposed algorithm can effectively enhance the clarity of a video frame, with satisfying subjective visual quality and PSNR value.